PREVALENCE OF GASTROINTESTINAL NEMATODES INFECTION IN BALI CATTLE CALVES AT BERINGKIT ANIMAL MARKET BADUNG REGENCY - Manik Mustika Jayanthi; Nyoman Adi Suratma; I Made Dwinata (Buletin Veteriner Udayana, 2024)
Calves infected with gastrointestinal nematodes can spread diseases to other livestock in a new environment, causing a decrease in quality, and financial losses for farmers. This study aims to determine the prevalence and intensity of infection, as well as the gastrointestinal nematodes infecting Bali cattle calves at the Beringkit Livestock Market, Badung Regency. The study used a floatation method to identify worm egg morphology and continued with the McMaster method to determine infection intensity. Out of 100 fecal samples examined, 65 samples were found positive for gastrointestinal nematode infection, resulting in a prevalence of 65% infection among Bali cattle calves at the Beringkit Livestock Market, Badung Regency. The identified nematodes were strongyle-type worms (64%) with an infection intensity of 203 ± 384 EPG, Strongyloides papillosus (10%) with an infection intensity of 100 ± 89 EPG, and Toxocara vitulorum (9%) with an infection intensity of 155 ± 287 EPG. It is concluded from this study that the prevalence of gastrointestinal nematode infections in Bali cattle calves at the Beringkit Livestock Market, Badung Regency was high with infection intensity falling into the mild category. Regular and continuous deworming is necessary as a control and prevention measure for gastrointestinal nematode infections in Bali cattle calves.